The Influence Of Capital Structure And Liquidity On Company Value PT. Campina Ice Cream Industry TBK For The 2018 – 2022 Period - Inawati, Apriliani; Yusnita, Rita Tri; Yuniar, Evilia Sri (Jurnal Pusat Manajemen, 2025)
This research aims to determine the influence of capital structure and liquidity on company value at PT. Campina Ice Cream Industry Tbk for the 2018-2022 period. The data used is secondary data in the form of the company's quarterly report for the 2018-2020 period obtained via the official website PT. Campina Ice Cream Industry Tbk campina.co.id. The research method used is a descriptive, quantitative analysis research method with a causality approach. The data analysis technique used is multiple regression analysis with SPSS 25 tools. The research results show that capital structure and liquidity simultaneously have a significant effect on company value at PT. Campina Ice Cream Industry Tbk for the 2018-2022 period. Capital structure partially has a significant effect on company value at PT. Campina Ice Cream Industry Tbk for the 2018-2022 period. And liquidity partially has a significant effect on company value at PT. Campina Ice Cream Industry Tbk for the 2018-2022 period.